Quality analysis of population-based information on cancer stage at diagnosis across Europe, with presentation of stage-specific cancer survival estimates: A EUROCARE-5 study. (October 2017) - ,; Hackl, M.; Zielonke, N.; Van Eycken, E.; Henau, K.; Valerianova, Z.; Dimitrova, N.; Sekerija, M.; Dušek, L.; Zvolský, M.; Mägi, M.; Aareleid, T.; et al.
Abstract: Background: Cancer registries (CRs) are fundamental for estimating cancer burden, evaluating screening and monitoring health service performance. Stage at diagnosis—an essential information item collected by CRs—has been made available, for the first time, by CRs participating in EUROCARE-5. We analysed the quality of this information and estimated stage-specific survival across Europe for CRs with good data quality. Data and methods: Sixty-two CRs sent stage (as TNM, condensed TNM or extent of disease) for 15 cancers diagnosed in 2000–2007. We assessed the quality, partly by comparing stage according to the three systems. We also developed procedures to reconstruct stage (categories: local, regional, metastatic and unknown) using information from all three systems, thus minimising the amount of missing information. Results: Moderate-to-excellent stage concordance was found for practically all 24 CRs, for which it was possible to compare at least two staging systems. However, since stage was often incorrectly assigned, and information on the presence/absence of metastases was often lacking, data on only 7/15 cancers from 34/62 CRs (15 countries) were of sufficient quality for further analysis. Cases diagnosed ≥70 years had more advanced (or lacking) stage– and worse stage-specific survival than those <70 years. Conclusions: Many European CRs collect and record reasonably accurate stage information. Others have difficulties. Both the completeness of primary data and the accuracy of stage coding need to be improved in order for CRs to fulfil their expanding roles in cancer control. We propose our stage reconstruction/checking procedures as a means of fully exploiting the stage information provided by EUROCARE CRs. More advanced (or lacking) stage at diagnosis plus poorer stage-specific survival in the elderly are worrying. Highlights: Sixty-two EUROCARE cancer registries sent us cancer stage at diagnosis for the first time. We extensively analysed the quality of that data for 15 solid cancers. For 34 registries and seven cancers, stage information was of sufficient quality. Personnel training and better quality primary data will increase the utility of stage data. Advanced stage and poor stage-specific survival in the elderly are worrying.